Development of Education-Based Tourism and Expansion of Marketing Networks in Kampung Batik Giriloyo - Audita Nuvriasari; Krisnita Candrawati; Gumirlang Wicaksono; Serlipuji Lestianengrum; Sucia Eka Ayunda (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2022)
Kampung Batik Giriloyo is one of the tourist villages and the center of the hand-drawn batik industry located in Kabupaten Bantul, DIY. The tourism village is managed by the Paguyuban Batik Tulis Giriloyo as a community service partner from the UMBY team. The management of the tourist village is good but there are still shortcomings, especially in the development of variants of educational tourism attractions and expansion of marketing networks. Partners have used information technology to market educational tours or batik products. However, partners are still limited in knowledge and skills to use on-line media as a means of promotion to expand their marketing network. The solution to these problems is to transfer science and technology to partners through outreach, training and advocacy or mentoring activities. The activities carried out are: (1). Educational Tourism Development Counselling, (2). Training on making accessories made of batik, (3) Training on creating a database of Cooperation partners, (4). Cooperation proposal making training, and (5). Online marketing training. The activity outputs are: (1). The addition of educational tourism variants through learning to make batik accessories and (2) Increasing the knowledge and skills of partners in the field of marketing and expanding the network of cooperation.